Crocus sativus L. in the treatment of mild to moderate depression: A double-blind, randomised and placebo controlled trial - AA Noorbala; N Tahmasebi-Pour; S Akhondzadeh; M Khani; AH Jamshidi (Institue of Medicinal Plants, ACECR, 2004)
Depression is a serious disorder in today's society. With estimates of lifetime prevalence as high as 21% of the general population in some developed countries. As a therapeutically plant, saffron it is considered an excellent stomach ailment and an antispasmodic, helps digestion and increases appetite. It is also used for depression in Persian traditional medicine. Our objective was to assess the efficacy of stigmas of Crocus sativus (saffron) in the treatment of mild to moderate depression in a 6-week double-blind, placebo controlled and randomized trial. Forty adult outpatients who met the Diagnostic and Statistical Manual of Mental Disorders, 4th edition for major depression based on the structured clinical interview for DSM IV participated in the trial. Patients have a baseline Hamilton Rating Scale for Depression score of at least 18. In this double-blind, placebo controlled, single-center trial and randomized trial, patients were randomly assigned to receive capsule of saffron 30 mg/day (BD) (Group 1) and capsule of placebo (BD) (Group 2) for a 6-week study. At 6 weeks, Crocus sativus produced a significantly better outcome on Hamilton Depression Rating scale than placebo (d.f.=1, F= 18.89, p<0.001). There were no significant differences in the two groups in terms of observed side effects. The results of this study indicate the efficacy of Crocus sativus in the treatment of mild to moderate depression. A large- scale trial is justified.